Fragmentos verdes na Avenida Paulista: análise dos espaços livres sob o viés do urbanismo biofílico. - Moraes, Dulce Ferreira de (2020)
From the perspective of sustainable urbanism and the biophilic approach, which is based on the existence of an inherent inclination to the human being to associate and feel well in contact with the natural environment, this dissertation has as its theme the relationship of society with nature - especially with vegetation - in public spaces. Avenida Paulista was chosen for study and research because it’s located in the central region of the city of São Paulo, characterized by the low rate of green coverage and densification of vertical buildings. The work presents applied research that identified and analyzed the presence of biophilic elements in free spaces for public use and the aspects of governance in relation to biophilia and environmental preservation. The study suggests that biophilia - the connection between people and nature - should be considered and incorporated into public policies and urban projects and can contribute to efforts aimed at the challenges of 21st century cities, like as actions to mitigate the effects of climate change and improve the health of the urban population.